Macroeconomic and Institutional Determinants of ASEAN Middle Income Trap: Evidence from 2014–2023 - Alfira Nabila; Jamzani Sodik; Didi Nuryadin (Universitas Ahmad Dahlan, Yogyakarta, 2026)
This study aimed to analyze the effect of Foreign Direct Investment (FDI), Human Development Index (HDI), Corruption Perception Index (CPI), and inflation on Gross National Income (GNI) per capita in 11 ASEAN countries during the period 2014–2023. In addition, this study evaluates the differences in GNI levels between countries that remain trapped in the Middle Income Trap (MIT) and those that have successfully escaped it. The method used was panel data regression with the Random Effect Model approach. The results showed that FDI and HDI have a significant positive effect on GNI per capita, whereas CPI has a significant negative effect. Inflation has no significant effect. The MIT dummy variable also has a significant negative effect, indicating that countries that remain in the MIT tend to have lower per capita income levels compared to countries that have successfully escaped. These findings reinforce the importance of the role of institutional quality and human development in increasing national income. This study contributes to the development economics literature by highlighting the importance of macroeconomic and institutional variables in explaining income disparities in the ASEAN region.